PERANCANGAN HUMAN RESOURCES INFORMATION SYSTEM BERBASIS WEB MENGGUNAKAN METODE WATERFALL - Muhammad Zaidan; M Fauzi Isputrawan (Universitas Teknokrat Indonesia, 2025)
The era of digital transformation has brought significant changes to human resource management across various organizations. Manual human resource management (HRM) at PT Infico Alumindo Indonesia has resulted in several issues, such as delayed attendance recap, disorganized leave data, and time-consuming payroll processes. Therefore, this study aims to design and implement a web-based Human Resources Information System (HRIS) using the Laravel framework and the waterfall method to improve HRM efficiency at PT Infico Alumindo Indonesia. This research employs the waterfall method, which consists of five stages: requirement analysis, system design, implementation, testing, and maintenance. Data collection techniques include direct observation at the company, interviews with company representatives particularly the Operational Director, and literature studies from various academic sources. The results of this study indicate that the developed HRIS successfully automates the attendance process through facial recognition technology and real-time location tracking. The attendance feature for sales personnel is enhanced with photo geotagging, displaying timestamps and real-time locations on the captured images. The leave management module is also systematically integrated, allowing supervisors to approve leave requests quickly and in a well-documented manner. The payroll feature is now directly connected to attendance data, sales attendance, monthly and daily wages, and overtime, enabling accurate and efficient payroll calculations. Additionally, the people development module supports periodic employee development tracking, including performance evaluations and job mutations.